2012
DOI: 10.5511/plantbiotechnology.12.0515b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Jatropha curcas lignins

Abstract: Lignins of Jatropha curcas organs were qualitatively and quantitatively characterized by thioglycolic acid, thioacidolysis, and nitrobenzene oxidation methods. e lignin content of the seed coat was 49.4%, and was the highest among various organs of the plant, while the stem had 15.9% lignin, within the range of usual lignin contents of angiosperm trees. Lignin aromatic components of all organs were composed of guaiacyl and syringyl units. Nitrobenzene oxidation indicated that the ratios of syringyl to guaiacyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Many of the Euphorbiaceae plants characterized in this study, for example, J. curcas, V. fordii (also known as the tung oil tree), A. moluccana (candlenut), and R. communis (castor oil plant), have attracted considerable research attention for their potential applications as feedstocks for biodiesel production (Sujatha et al, 2008;Vega-Sánchez and Ronald, 2010;Abdulla et al, 2011). Studies describing chemical and/or even NMR analysis of seed coats in these plants have consequently been reported recently by other groups (Klein et al, 2010;Martin et al, 2010;Watanabe et al, 2012;Wever et al, 2012;Yamamura et al, 2012). However, the presence of C lignin in the seed coats has remained unclear, possibly because the notion that polymers could result from caffeyl alcohol polymerization has only been recently recognized (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Many of the Euphorbiaceae plants characterized in this study, for example, J. curcas, V. fordii (also known as the tung oil tree), A. moluccana (candlenut), and R. communis (castor oil plant), have attracted considerable research attention for their potential applications as feedstocks for biodiesel production (Sujatha et al, 2008;Vega-Sánchez and Ronald, 2010;Abdulla et al, 2011). Studies describing chemical and/or even NMR analysis of seed coats in these plants have consequently been reported recently by other groups (Klein et al, 2010;Martin et al, 2010;Watanabe et al, 2012;Wever et al, 2012;Yamamura et al, 2012). However, the presence of C lignin in the seed coats has remained unclear, possibly because the notion that polymers could result from caffeyl alcohol polymerization has only been recently recognized (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Its intrinsic monomer units have been determined as 1040 μmol g -1 from the NBO method (Tables S2 and S3), which is widely used in literature as a standard protocol to analyse lignin monomers connected by C-O bonds (including but not limited to β-O-4 linkage). 23,38,39 The C-C linkage in lignin cannot be cleaved in the NBO method, thus making the comparison straightforward for the present study. It has been reported that the theoretical amount of lignin monomers coincides with the square of the fraction of ether bonds in the lignin structure, and that of birch lignin varies from 45% to 58%.…”
Section: One-pot Conversion Of Lignin Into Monocyclic Hydrocarbonsmentioning
confidence: 99%
“…Ground leaf tissues were washed serially with water, 80% ethanol, and acetone, and freeze dried. The washed leaf tissues (~3 mg) were then subjected to analytical thioacidolysis according to the method described by Yamamura et al (2012). The released lignin monomers were derivatized with N,O-bis(trimethylsilyl)acetamide and quantified by gas chromatography-mass spectrometry, using 4,4′-ethylenebisphenol as an internal standard (Yue et al, 2012).…”
Section: Thioacidolysis-based Lignin Composition Analysismentioning
confidence: 99%